The Role of Leadership in Improving the Quality of Healthcare Services at Community Health Centers : A Systematic Review - Emma Puspita Kartikasari; Arih Diyaning Intiasari; Budi Aji (Green Publisher Indonesia, 2024)
Various factors related to the quality of health services in primary health care facilities include health care providers, organizational and leadership factors, and environmental factors (internal and external). A leadership role is required, especially in terms of company-wide coordination and of course motivation. This study used a systematic review method. Electro databases used included Google Scholar, Pubmed, & Garuda Journal using the key terms